Expression of p16 Within Myenteric Neurons of the Aged Colon: A Potential Marker of Declining Function - Palmer, Alexandra; Epton, Sarah; Crawley, Ellie; Straface, Marilisa; Gammon, Luke; Edgar, Meghan M.; Xu, Yichen; Elahi, Shezan; Chin-Aleong, Joanne; Martin, Joanne E.; Bishop, Cleo L.; Knowles, Charles H.; et al. (Frontiers in Neuroscience, 2021)
Human colonic neuromuscular functions decline among the elderly. The aim was to explore the involvement of senescence. A preliminary PCR study looked for age-dependent differences in expression of CDKN1A (encoding the senescence-related p21 protein) and CDKN2A (encoding p16 and p14) in human ascending and descending colon (without mucosa) from 39 (approximately 50 : 50 male : female) adult (aged 27-60 years) and elderly donors (70-89 years), in addition to genes from different ageing pathways (e.g., inflammation, oxidative stress, autophagy) and cell-types (e.g., neurons, neuron axonal transport). Unlike CDKN1A, CDKN2A (using primers for p16 and p14 but not when using p14-specific primers) was upregulated in both regions of colon. Compared with temporal age, more genes were positively associated with increased CDKN2A expression (respectively, 16 and 5 of 44 genes studied for ascending and descending colon). Confirmation of increased expression of CDKN2A was sought by immunostaining for p16 in the myenteric plexus of colon from 52 patients, using a semi-automated software protocol. Contrary to expectation, the results showed increased staining not within the proliferative glial cells (S100 stained), but in the cytoplasm of myenteric nerve cell bodies (MAP2 stained, with identified nucleus) of ascending, but not descending colon of the elderly, and not in the cell nucleus of either region or age group (5,710 neurons analyzed: n = 12-14 for each group). It was concluded that increased p16 staining within the cytoplasm of myenteric nerve cell bodies of elderly ascending (but not descending) colon, suggests a region-dependent, post-mitotic cellular senescence-like activity, perhaps involved with ageing of enteric neurons within the colon.